2001
DOI: 10.1002/hed.1064
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative capacity in head and neck cancer

Abstract: (1) In general, no significant differences in proliferation parameters were observed with respect to site of origin. (2) Aneuploid head and neck tumors have a higher proliferative capacity than diploid ones, they might benefit most from accelerated irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The main cause of failure of locally advanced HNC surgery is local recurrence caused by regrowth of tumor cell residues [14]. Radiotherapy has become an important nonsurgical treatment for different stages of HNC, especially advanced lesions that usually recur in local areas [24]. Most clinical practices also suggest that the main cause of failure by CFRT for malignant tumors is local recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The main cause of failure of locally advanced HNC surgery is local recurrence caused by regrowth of tumor cell residues [14]. Radiotherapy has become an important nonsurgical treatment for different stages of HNC, especially advanced lesions that usually recur in local areas [24]. Most clinical practices also suggest that the main cause of failure by CFRT for malignant tumors is local recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, the majority of clinical practices have suggested that the failure of malignant tumor treatment by CF RT is primarily due to local recurrence. Furthermore, Struikmans et al40 have also shown that the accelerated proliferation of living tumor stem cells during RT is a primary cause for failures in the treatment of squamous cell carcinoma of the digestive and upper respiratory tracts. Therefore, inhibition of the accelerated repopulation of the tumor stem cells is a key factor in improving the survival and local control rates.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, local recurrence is the important cause of treatment failure of esophageal squamous cell carcinoma. Research has suggested that accelerated repopulation of the tumor during radiotherapy is one of the major reasons for treatment failure in squamous cell carcinoma of the upper respiratory and digestive tracts 22 . In order to improve the local control and survival, one goal of treatment is to limit the extent of esophageal carcinoma cell regeneration that occurs during RT.…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested that accelerated repopulation of the tumor during radiotherapy is one of the major reasons for treatment failure in squamous cell carcinoma of the upper respiratory and digestive tracts. 22 In order to improve the local control and survival, one goal of treatment is to limit the extent of esophageal carcinoma cell regeneration that occurs during RT. Reports show that accelerated repopulation usually begins 3-5 weeks after the start of RT.…”
Section: Discussionmentioning
confidence: 99%